High-Dimensional Semiquantum Cryptography - Iqbal, Hasan; Krawec, Walter O. (IEEE transactions on quantum engineering, 2020)
A semiquantum key distribution (SQKD) protocol allows two users, one of whom is restricted in their quantum capabilities to being nearly classical, to establish a shared secret key, secure against an all-powerful adversary. The study of such protocols helps to answer the fundamental question of "how quantum" must a protocol be to gain an advantage over classical communication. In this article, we design a new SQKD protocol using high-dimensional quantum states and conduct an information theoretic security analysis. We show that, similar to the fully quantum key distribution case, high-dimensional systems can increase the noise tolerance in the semiquantum case. Furthermore, we prove several general security results which are applicable to other (S)QKD protocols (both high-dimensional ones and standard qubit-based protocols) utilizing a two-way quantum channel.